Arginine side chain stacking with peptide plane stabilizes the protein helix conformation in a cooperative way. Issue 6 (30th March 2018) - Wang, Jia; Chen, Jingfei; Li, Jingwen; An, Liaoyuan; Wang, Yefei; Huang, Qingshan; Yao, Lishan
Abstract: A combined experimental and computational study is performed for arginine side chain stacking with the protein α‐helix. Theremostability measurements of Aristaless homeodomain, a helical protein, suggest that mutating the arginine residue R106, R137 or R141, which has the guanidino side chain stacking with the peptide plane, to alanine, destabilizes the protein. The R‐PP stacking has an energy of ∼0.2‐0.4 kcal/mol. This stacking interaction mainly comes from dispersion and electrostatics, based on MP2 calculations with the energy decomposition analysis. The calculations also suggest that the stacking stabilizes 2 backbone‐backbone h‐bonds ( i → i ‐4 and i ‐3→ i ‐7) in a cooperative way. Desolvation and electrostatic polarization are responsible for cooperativity with the i → i ‐4 and i ‐3→ i ‐7 h‐bonds, respectively. This cooperativity is supported by a protein α‐helices h‐bond survey in the pdb databank where stacking shortens the corresponding h‐bond distances.